PROSEDUR PENERJEMAHAN ISTILAH BIDANG LINGUISTIK DALAM GLOSARIUM - Meryna Afrila; Emzir Emzir; MIftahulkhairah Anwar (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Linguistic terms are somehow universal, although in some language those terms are not exactly mutual. Considering some linguistics differences among languages, there must be a careful consideration in translating linguistics terms. This research is conduct to analyze the translation process of English linguistics terms into Indonesian. Which translation procedures is applied in linguistics terms in glossary. In analyzing the data, the writer applies the theory Pedoman Umum Pembentukan Istilah (PUPI), diagram V translation Newmark’s methods, and other translation procedures contains of: (1) transposition, (2) modulation, (3) descriptive equivalent, (4) naturalisation, (5) paraphrase, (6) reduction and expansion, (7) compensation, (8) footnote translation, (9) recognised translation, (10) cultural equivalent, (11) transference, (12) calque, and (13) couplets. This is a qualitative research, and the source data comes from Glosarium Badan Pengembangan Bahasa dan Perbukuan (linguistic term only). Data collecting technique used in this research is document analysis. Having analyzed twenty entries from the glossaries, the writer found that there are some kind of technique used in translating the linguistic terms into the target language.